Originally Posted by **KAF33**

Unfortunately, my last question seems to be unsolvable, but I came across another one when trying to work out my model...

After simplifying the symbols in order to make it easier to type/read I have the equation

R= [(EKT/h)(e^(S-H/T)/R)]/[1+(e^(S1-H1/T)/R)+(e^(S2-H2/T)/R)

and then they substituted the term φ=S+ ln(KE/h) so that

R=[Te^(φ-H1/T)/R]/[1+(e^(S1-H1/T)/R)+(e^(S2-H2/T)/R)

My question is how you are able to arrange things in the numerator so that you can assign φ=S+ln(KE/h)... After arranging things I can get φ=S+Rln(EK/h), but I don't know how to get rid of that extra R!